Systematics of the genus Gmelina L. (Lamiaceae) in Southeast Asia - Harun-ur-Rashid, Mohammad (Trinity College (Dublin, Ireland). Department of Botany, 2009)
The systematics of Gmelina is investigated using morphological, anatomical, palynological and molecular data.The genus is revised for Southeast Asia and 31 taxa are recognised consisting of 26 species, 1 subspecies, and 4 varieties; with a very few exceptions (5 species) all are endemic to this territory. Based on calyx characters a revised new infrageneric classification is proposed. The genus is divided in two sections: section Asiaticum M. H. Rashid & J. Parnell and section Annameticum M. H. Rashid & J. Parnell.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.